Protección mixta de los derechos humanos en la Corte Constitucional de Colombia en relación con los derechos de los pueblos indígenas: el principio pro homine como centro de gravedad (2020)
The rights of indigenous peoples have acquired multilevel protection under the understanding that both the Inter-American Human Rights System (IAHRS) and the domestic law of the Colombian State provide guarantees for their rights. The constitutionality block integrated by the American Convention on Human Rights (ACHR) requires that domestic regulations do not contravene the provisions of the Convention. In this regard, the Colombian Constitutional Court has made progress in the recognition of both individual and collective rights for indigenous peoples in Colombia, recognition that, despite being of great importance, is insufficient as serious violations of the human rights of these subjects of special protection persist.